Steps Toward a Cognitive Science of Religion - Oviedo, Lluís (Zygon, 2008)
Abstract. The article chronicles the different panels devoted tothe cognitive science of religion at the meeting of the Society for the Scientific Study of Religion (SSSR) in Tampa, Florida, in November 2007. The aim is to verify the state of this subdiscipline and to check how much this work-in-progress affects the present state of the dialogue between science and religion. Several signs point to a positive development in this scientific branch and favor a sound reception in theology, which should not ignore the new research.